Possible density-dependence in an expanding population of Greylag Goose Anser anser in south Sweden - Nilsson, Leif (Wildfowl, 2016)
Neck-banded Greylag Geese Anser anser breeding in southwest Sweden were studied from 1984–2012 inclusive, to determine annual variation in the number of breeding pairs, reproductive success and survival rates, as part of a larger programme of monitoring individual geese across the Nordic countries. Numbers breeding in the study area increased from 120 pairs in 1984 to 1,240 pairs in 2008, followed by a decrease to about 800 pairs. As the number of nesting pairs of Greylag Geese increased, the proportion of pairs producing young decreased, suggesting densitydependence effects on the production of young. The decline in the proportion of breeding pairs occurred later at a lake thought to offer better feeding areas for the young than at a second lake in the study area. There was no marked decrease in the mean brood size among productive pairs, only a slight decrease in the fledging rate. There was also no clear trend during the study in first-year survival rates for geese neck-banded at fledging.